2018
DOI: 10.1007/s10549-018-4907-7
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory cytokines and growth factors in human milk: an exploratory analysis of racial differences to inform breast cancer etiology

Abstract: This exploratory study demonstrated the feasibility of measuring pro-inflammatory cytokines, adipokines, and angiogenesis factors in human milk, and revealed higher levels of some pro-inflammatory factors, as well as increased leptin levels, among Black as compared with White women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 41 publications
(38 reference statements)
1
36
0
Order By: Relevance
“…These factors may affect the cytokine levels of human milk. In previous study, elevated maternal BMI was significantly associated with increased levels of some kind of cytokines in their milk (20). In this study, these factors showed similar values between the two groups except for IgA.…”
Section: Discussionmentioning
confidence: 86%
“…These factors may affect the cytokine levels of human milk. In previous study, elevated maternal BMI was significantly associated with increased levels of some kind of cytokines in their milk (20). In this study, these factors showed similar values between the two groups except for IgA.…”
Section: Discussionmentioning
confidence: 86%
“…Several epidemiological studies have reported that IBD mothers receiving therapy should not be discouraged from nursing their children and nursing may even provide a protective effect against disease flare in the postpartum year, 6,22 whereas other studies have not found such associations. 29,30 Breastfeeding is known to provide significant health benefits to infants, including the transmission of protective antibodies, 31 cytokines, 15,32 immunoreactive biochemicals and leukocytes. 20,33 Unlike most mammals, human breast milk antibodies that are transferred from mother to infant do not enter the child's circulation in large amounts.…”
Section: Discussionmentioning
confidence: 99%
“…(101). Interestingly, other studies have shown that milk from healthy black women may contain higher levels of IL-1β than from white women even when controlled for BMI (102), which strengthens the hypothesis that increased inflammation within the breast of black women compared with white women may be linked to the higher rates of early onset breast cancer in black women (103). Therefore, potential strategies to reduce racial disparities in breast cancer risk could be through interventions such as short courses of anti-inflammatory agents (102).…”
Section: Serum Cytokine Profile In Breast Cancer Patients Of Different Racial/ethnic Backgroundsmentioning
confidence: 98%